Aldosterona e apetite ao sódio: uma nova evidência para um antigo efeito - Formenti, Silmara [UNIFESP] (2009)
Aldosterone is a mineralocorticoid hormone that acts within the central nervous system (CNS) to induce sodium appetite; however the central mechanism involved in this effect is poorly understood. More recently, neuroanatomical studies identified a unique group of aldosterone-sensitive neurons in the nucleus of the solitary tract (NTS) near to the fourth cerebral ventricle (4V), which are activated in association with sodium appetite. In the present study we sought to investigate if (1) chronic infusion of aldosterone into the 4V or lateral ventricle (LV) may induce the sodium appetite, and if (2) a single microinjection of a selective mineralocorticoid receptor (MR) antagonist, RU 28318, into the 4V or LV would be able to affect the sodium intake induced by different protocols. Male Wistar Hannover rats were implanted with a guide cannula into the 4V and were infused with vehicle (1% ethanol-saline; n= 5) or aldosterone (1, 10 or 100 ng/h; n= 5) and those rats implanted with cannula into the LV were infused with aldosterone (10 or 100 ng/h; n= 4), during 6 days. The infusion of aldosterone (1, 10 or 100 ng/h) into the 4V significantly increased the 0.3 M NaCl intake compared with baseline levels. In addition, aldosterone (10 or 100 ng/h) induced a robust dose-dependent daily 0.3 M NaCl intake (up to 45.8 ± 14.9 and 129.8 ± 5.5 mL/24 h, respectively), that returned to the baseline levels few hours after stopping the infusion. However, the infusion of aldosterone (10 or 100 ng/h) into the LV failure to induce any significant 0.3 M NaCl intake. The water intake was reduced by the infusion of aldosterone (10 or 100 ng/h) into the 4V when compared with vehicle and 1 ng/h, but the food intake was not affected. In the next experiment, rats implanted with a guide cannula into the 4V or LV were treated according to following protocols: depletion with furosemide (20 mg/kg, s.c.; n= 6) 24 h before the experiment, or sodium deprivation for 9 days (n= 4- 5), or treatment with DOCA (2 mg/dia, s.c.; n= 4-7) for 7 days. At the end of the treatment rats received a single microinjection of RU 28318 (100 or 500 ng/2 ìL) or vehicle (1% ethanol-saline, 2 ìL) and after 2 h the intake test started. The single microinjection of RU 28318 (100 ng/2 ìL) into the 4V significantly reduced the 0.3 M NaCl intake induced by previous treatment of furosemide (5.6 ± 0.8 vs. vehicle 12.2 ± 1.7 mL/2 h, p< 0.05) or sodium deprivation protocol (1.2 ± 0.6 vs. vehicle 9.5 ± 2.6 mL/2 h, p< 0.001). However, the same dose of RU 28318 injected into the LV was not able to affect the furosemide induced-0.3 M NaCl intake (14.8 ± 2.8 vs. vehicle 15.1 ± 3 mL/2 h, p> 0.05). Surprisingly, the microinjection of RU 28318 (500 ng/2 ìL) into the 4V failure to reduce the 0.3 M NaCl intake induced by chronic treatment with DOCA (13.6 ± 2.7 vs. vehicle 11.1 ± 2.3 mL/2 h, p> 0.05). Our results are the first functional evidence to show that chronic infusion of aldosterone into the 4V, but not into the LV, induce a robust dose-dependent sodium appetite. These results are reinforced by our studies using MR antagonist, which a single microinjection of RU 28318 into the 4V significantly reduced the sodium intake induced by furosemide or sodium deprivation. These data confirm the central action of aldosterone in the sodium appetite control, and together with previous neuroanatomical studies suggest that hindbrain areas around of 4V are the preferential site of action for aldosterone to induce sodium appetite.